RESPON PRODUKTIVITAS PADI SAWAH DENGAN PEMBERIAN KOMPOS SAMPAH KOTA DI DESA ARAS KABU - Fitra Syawal Harahap; Rauf Abdul; Hasibuan Rosmidah; Rendi Fitra Yana; Iman Arman (Agrica Ekstensia, 2020)
The aim of the research was to obtain the best dose of municipal solid waste compost so as to increase rice growth and yield in Aras Kabu Village, Beringin District, Deli Serdang Regency. This research was conducted in Aras Kabu Village, Beringin District, Deli Serdang Regency with an altitude of 11 meters above sea level. This research was conducted in February 2020 until May 2020. This study used a non factorial randomized design with a dose of organic matter (B) City Waste Compost, consisting of 5 (five) levels, namely B0 = Control B1 = 1.5% ( 28.70 tons / ha), B2 = 3% (57.40 tons / ha), B3 = 4.5% (96.10 tons / ha), B4 = 6% (104.8 tons / ha) Research Results with the provision of organic matter compost municipal waste as much as 96.10 to 104.80 tons / ha significant growth in plant height (cm), the number of productive tillers. Number of unhulled rice / panicles, Percentage of unhulled rice / panicles and Paddy Rice Production Dry rice yield / plot (kg), Weight of 1000 dry grains of harvested rice (grams) with inpari 10 varieties in Aras Kabu Village, Beringin District, Deli Serdang Regency.